(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
Today, increasing the level of economic literacy of the population in the neighborhood system is considered one of the issues of global importance, and in the process of calculating loans, taxes, compound interest and using financial goods and services, it is necessary to properly manage household finances in the future, to correctly manage future incomes. In order to be able to distribute loans, he must have an understanding of credit and its repayment methods.